2018
DOI: 10.3390/universe4020035
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Scattering of Radiation on Wormholes

Abstract: Significant progress in the development of observational techniques gives us the hope to directly observe cosmological wormholes. We have collected basic effects produced by the scattering of radiation on wormholes, which can be used in observations. These are the additional topological damping of cosmic rays, the generation of a diffuse background around any discrete source, the generation of an interference picture, and distortion of the cosmic microwave background (CMB) spectrum. It turns out that wormholes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…We also obtained embedding diagrams for wormhole solutions and the behavior of timelike and null geodesics in wormhole configuration were discussed. The study of wormhole geodesics is of great importance as it could help us to figure out possible observational effects that arise as a result of the scattering of particles on wormholes [56]. Likewise, such an investigation provides a promising way to test modified theories of gravitation as well as sufficient incentives for scientists towards probing wormhole structures in the universe.…”
Section: Discussionmentioning
confidence: 99%
“…We also obtained embedding diagrams for wormhole solutions and the behavior of timelike and null geodesics in wormhole configuration were discussed. The study of wormhole geodesics is of great importance as it could help us to figure out possible observational effects that arise as a result of the scattering of particles on wormholes [56]. Likewise, such an investigation provides a promising way to test modified theories of gravitation as well as sufficient incentives for scientists towards probing wormhole structures in the universe.…”
Section: Discussionmentioning
confidence: 99%
“…For small throats of wormholes (of the galaxy size or less), the additional images are very small and cannot be directly observed. Indeed, as demonstrated in Reference [28], in the flat model the intensity of an image I has the order I ∼ R 2 L 2 I 0 , where R is the characteristic radius of the throat and L is the distance between the throat center and the original source and the ratio R 2 L 2 ≤ 1. It reaches the order of R 2 L 2 ∼ 1 only for very large throats.…”
Section: Introductionmentioning
confidence: 93%
“…However, our previous investigation have shown that observational effects of a distribution of wormholes are very well hidden under analogous effects produced by ordinary matter e.g., see Refs. [30,31]. The only exclusion may be the noise (stochastic background) produced by the scattering of emitted by binaries gravitational waves on wormholes [32].…”
Section: Introductionmentioning
confidence: 99%